Spatiotemporal Distribution, Meteorological Influence, and Potential Sources of Air Pollution over Hainan Island, China - Yuying Yu; Huayuan Zhou; Zhizhong Zhao; Yunhua Chang; Dan Wu; Zhongqin Li; Feiteng Wang; Mengyang Fang; Xi Zhou (Atmosphere)
Data on particulate matter, gaseous pollutants, and AQI values from three cities (Haikou, Sanya, and Danzhou) between January 2018 and December 2022 were obtained in order to analyze the spatiotemporal distribution characteristics of air pollution, the correlation between pollutants with meteorological conditions, and the potential sources in Hainan Island. The spatiotemporal distribution’s characteristics demonstrated that the annual mean concentrations of SO2, NO2, CO, O3, PM10 and PM2.5 were 4.34 ± 1.11 μg m−3, 9.87 ± 1.87 μg m−3, 0.51 ± 0.06 mg m−3, 73.04 ± 6.36 μg m−3, 27.31 ± 3.63 μg m−3, and 14.01 ± 2.02 μg m−3, respectively. The yearly mean concentrations were trending downward in the past few years and were below the National Ambient Air Quality Standard (NAAQS) Grade II. Summer was the season with the lowest concentrations of all pollutants (3.84 μg m−3, 7.34 μg m−3, 0.42 mg m−3, 52.80 μg m−3, 18.67 μg m−3 and 8.67 μg m−3 for SO2, NO2, CO, O3, PM10 and PM2.5, respectively), and afternoons were the time with the lowest concentrations of pollutants (except for 78.04 μg m−3 for O3). The influence of meteorological conditions on pollutants was examined: there was a prominent positive correlation between temperature and O3 in summer, and relative humidity largely influenced the concentrations of PM. The pollution in Hainan was affected more by regional transport; according to the backward trajectory results, Hainan is susceptible to air masses from Guangdong and Fujian to the northeast, the Indochina Peninsula to the southwest, and the South China Sea to the southeast. The results of PSCF and CWT analyses indicated that Guangdong, Jiangxi, Hunan, and Fujian were the primary potential sources of PM2.5 and O3.